2023
DOI: 10.3390/nu15040948
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Hub Long Noncoding RNAs and mRNAs in High Fat Diet Induced Liver Steatosis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is considered the most prevalent chronic liver disease, but the understanding of the mechanism of NAFLD is still limited. The aim of our study was to explore hub lncRNAs and mRNAs and pathological processes in high-fat diet (HFD)-induced and lycopene-intervened liver steatosis. We analyzed the gene profiles in the GSE146627 dataset from the Gene Expression Omnibus (GEO) database to identify differentially expressed lncRNAs and mRNAs, and we constructed coexpression netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…HOMA‐IR, an essential indicator of systemic IR, is now elevated with HFD induction and relieved with LQ treatment. Previous studies have reported that the NAFLD model constructed by HFD is a high‐fat‐feeding obesity model, but the model is widely used in NAFLD research (Lahbib et al, 2015; Sui et al, 2023; Yan et al, 2022). With our current results, we found that LQ affected not only lipid metabolism but also glucose metabolism, so this suggests that the improvement of fatty liver by LQ may be accomplished through glucolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…HOMA‐IR, an essential indicator of systemic IR, is now elevated with HFD induction and relieved with LQ treatment. Previous studies have reported that the NAFLD model constructed by HFD is a high‐fat‐feeding obesity model, but the model is widely used in NAFLD research (Lahbib et al, 2015; Sui et al, 2023; Yan et al, 2022). With our current results, we found that LQ affected not only lipid metabolism but also glucose metabolism, so this suggests that the improvement of fatty liver by LQ may be accomplished through glucolipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Liu and colleagues additionally discovered that lncSNHG6 activates the interaction between mTOR and fas-associated factor family member 2 at ER-lysosome contacts and enhances the recruitment of mTORC1 to lysosomes in a cholesterol-dependent manner, further promoting the transition from MASLD to HCC [ 125 ]. Additionally, some lncRNA (Tacc1, lnc027912, Mef2c) are also involved in the reprogramming of lipid metabolism, such as mTOR/AMPK/SREBP 1c regulation in MASLD [ 174 , 175 ]. In addition, ncRNA can regulate the expression of FA transporter-related proteins.…”
Section: Interactions Between Epigenetic Modifications and Hcc Cell M...mentioning
confidence: 99%
“…Liu et al have further identified the long ncRNA (lncRNA) SNHG6 as an enhancer of cholesterol-dependent mTORC1 lysosomal recruitment and activator of FAF2-mTOR interaction at ER-lysosome contacts, which increased progression from NAFLD to HCC [ 148 ]. In addition, other long lncRNAs (lnc027912, Smarca2, Tacc1, Flywch1, and Mef2c) are involved in the regulation of the lipid accumulation, and inflammatory and metabolic pathways, such as mTOR/AMPK/SREBP1c signaling in NAFLD [ 149 , 150 ]. In addition to these results, Xu et al recently demonstrated by applying the bioinformatic analysis that PTEN-induced putative kinase 1 (PINK1)-mediated mitophagy is inhibited in NASH mouse liver with fibrosis via the axis of upstream circular RNA 608 (circ608)-microRNA 222 (miR222)-PINK1 (circ608 inhibiting miR222) through mTOR and Wnt pathways [ 151 ].…”
Section: New Therapeutic Approaches and Molecular Targets In Nafld/na...mentioning
confidence: 99%